PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK MENGGUNAKAN MODEL MAKE A MATCH DI KELAS IV SDN 196/II TAMAN AGUNG - shinta elviana; randi eka putra; abdullah (STKIP Subang, 2025)
The problem in this study is the low learning process and outcomes of students inmathematics in fourth grade at SDN 196/II Taman Agung. This study aims toimprove the learning process and outcomes of students in fourth grade at SDN196/II Taman Agung, Bathin III District.This type of research is classroom actionresearch, examining the situation and conditions of the teaching and learningprocess at school. This study was conducted with 18 students in the secondsemester of the 2024/2025 academic year. The study consisted of two cycles,each consisting of planning, implementation, observation, and reflection. Data forthis study were collected using quantitative and qualitative data analysistechniques.The results of this study can be explained as follows: (1) Theapplication of the make-a-match learning model, as seen from the learningprocess and outcomes in cycle I, with an average of 49.44%, increased in cycle II,with an average of 86.66%. (2) The implementation of the make a match learningmodel is seen from the observation sheet, namely cycle I meeting I from theeducator aspect with a value range of 88.23% while cycle I meeting II with a valuerange of 94.11% and cycle II meetings I and II 100% and the student aspect ofcycle I meeting I with an average value of 68.94% while cycle I meeting II with avalue range of 74.16% and in cycle II there was an increase in the student aspectof cycle I meeting I reaching an average value of 80.55% while cycle II meeting IIreached an average of 92.15% with a very good category. It can be concluded thatthe implementation of the make a match learning model can improve the processand results of learning mathematics.